Defamation Through Social Media Based on Law Number 19 of 2016 Regarding Information And Electronic Transactions (Case Study of Medan District Court Decision No1/Pid.sus/2019/PN.Mdn.) - Deded Syahputra (CERED Indonesia Institute, 2023)
Legal issues that are often faced by people in the current era of information disclosure are related to the delivery of information, communication and/or data electronically, especially related to hate speech or defamation, one of which was committed by Abdul Hasiolan Siregar with Decision Number Number 1/Pid. sus/2019/PN. Mdn. The mistake started at the investigation stage. It is true that structurally the defendant is the chief editor of the Medanseru.co media and this is based on the Press Law, so the defendant must be responsible for all editorial content on the Medanseru.co media page. However, the facts in the trial revealed that the online media medanseru.co was not officially registered on the Kominfo website, meaning that Medanseru.